2013
DOI: 10.1139/cjce-2012-0230
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties and hydration behavior of portland cement mortars containing calcined red mud

Abstract: Red mud (RM) is a solid waste derived from processing bauxite ore to produce alumina and is considered a hazardous waste due to its high pH. This paper describes the use of untreated mud and after calcination at distinct temperatures (450, 650, and 1000 °C) to attempt to improve its reactivity in cement mortars. In the formulations, Portland cement was replaced with up to 30 wt% red mud, and the addition of the red mud changed the hydration process, setting time, and workability. The temperature of hydration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 29 publications
3
10
0
2
Order By: Relevance
“…As shown in Figure 7, the reference Portland cement does not qualify as a pozzolanic material because the cement alone is not pozzolanic. It is the addition of the pozzolan in the presence of water that binds the calcium hydroxide that is formed by the cement hydration and lowers the calcium oxide content of the liquid phase of the cement paste 8,9,17 . The CaO and OH -ion concentrations decrease in the solution when SCBA is added, and a clear pozzolanic action is observed for mixtures containing SCBA independent of the calcination temperature of the ash.…”
Section: Verification Of Pozzolanic Activity By Chemical Test Methodsmentioning
confidence: 99%
“…As shown in Figure 7, the reference Portland cement does not qualify as a pozzolanic material because the cement alone is not pozzolanic. It is the addition of the pozzolan in the presence of water that binds the calcium hydroxide that is formed by the cement hydration and lowers the calcium oxide content of the liquid phase of the cement paste 8,9,17 . The CaO and OH -ion concentrations decrease in the solution when SCBA is added, and a clear pozzolanic action is observed for mixtures containing SCBA independent of the calcination temperature of the ash.…”
Section: Verification Of Pozzolanic Activity By Chemical Test Methodsmentioning
confidence: 99%
“…Red mud used as a partial replacement of 25 %, 50 % of cement, which shown 18 %, 36 % of lesser compressive strength of mortar with reference to the controlled sample after 28 days curing [45]. The enhancement of strength at early age is, because of rate hydration is more in the red mud based concrete at an early age [46][47][48][49]. Another study Tsakiridis et al, (2004), reported that reason for increasing strength at early ages is red mud is increased hydration process rapidly due to filling effect of red mud particle in the concrete [26].…”
Section: Red Mud Used In Cement Productionmentioning
confidence: 99%
“…The presence of bauxite can improve the strength properties and workability of cementituos system due to its Pozzolanic reactivity, reacting with calcium hydroxide and producing additional gel (Soroshian and Won, 1995). According to Ribeiro et al (2013), addition of bauxite changed the hydration process, setting time, and workability, and signifi cantly altered important properties of Portland cement.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%